Paternal acrylamide exposure induces transgenerational effects on sperm parameters and learning capability in mice. (March 2022) - Zhang, Hang; Shan, Lidong; Aniagu, Stanley; Jiang, Yan; Chen, Tao
Abstract: Acrylamide (AA) has been shown to have neurological and reproductive toxicities, but little is known about transgenerational effects of AA. In this study, male C57BL/6 mice were exposed to AA (0.01, 1, 10 μg/mL) and its metabolite glycidamide (GA, 10 μg/mL) in drinking water, which were then mated with unexposed female mice to produce F1 and F2 generations. We found that both AA and GA at high concentrations decreased sperm motility in F0 mice and increased sperm malformation rates in mice from all the three generations. In addition, AA and GA increased sperm reactive oxygen species as well as decreased serum testosterone levels, and increased the escape latency time in exposed mice and their offspring. We further found that AA-induced mRNA expression changes in the hippocampus of F0 mice persist to the F2 generation. In the sperm of F0 mice, AA induced significant DNA methylation changes in genes involved in neural and reproduction; the mRNA expression levels of Dnmt3b, a DNA methyltransferase, were dramatically decreased in the testes of F0 and F1 mice. In conclusion, our study indicates that paternal AA exposure leads to DNA methylation-mediated transgenerational adverse effects on sperm parameters and leaning capability in mice. Graphical abstract: Image 1 Highlights: AA and GA induced transgenerational changes on sperm parameters in mice. AA and GA increased sperm ROS and decreased serum testosterone in all the three generations. AA and GA increased the escape latency time of mice in all the three generations. AA disturbed mRNA expression profile in the hippocampus of F0 mice. AA induced DNA methylation changes in the sperm of F0 mice.